Offshore aquaculture in China - Lina Long; Huang Liu; Mingchao Cui; Chenglin Zhang; Chong Liu (Reviews in Aquaculture, 2024)
The mariculture industry is planning to move offshore due to the decline of China's inshore fishery resources, the deterioration of the water environment, inefficient industrial structure and other influencing factors. This article first analyses the imbalance between supply and demand of aquatic products, the development space of offshore aquaculture and the supporting policies, thereby concluding that China has significant potential to develop offshore aquaculture. Subsequently, the development status of offshore aquaculture in China is examined. The research progress of China's offshore aquaculture facilities, marine hydrology, environmental carrying capacity, aquaculture technology and the status of aquaculture operation equipment are also summarized. Furthermore, the problems existing in the development of offshore aquaculture are pointed out. On this basis, future development ideas for China's offshore aquaculture can be planned in terms of sea area layout, optimized and improved seed production systems, and research and development of offshore aquaculture technology and pellet feed. The relationship between the development of offshore aquaculture and ecological protection should be coordinated. Additionally, an energy security system can be built based on clean energy, and the development of related industries can be driven through the complementary industrial division of labour. The present work aims to provide a reference for promoting the development of offshore aquaculture in China.